PLANNING OF DOMESTIC WASTEWATER SANITATION SYSTEM AFTER EARTHQUAKE DISASTER WANGUNJAYA VILLAGE, CUGENANG SUB-DISTRICT, CIANJUR REGENCY - Faskal Ramadhan, Muhammad
The problem faced by Wangunjaya Village, Cugenang Sub-district, especially in the earthquakeaffected area, is the destruction of sanitation facilities for domestic wastewater treatment. This can affect public health conditions, due to poor environmental health quality. Post-disaster sanitation is a potential method to be implemented in areas affected by natural disasters because it requires the ability to work together between policy makers, communities and other stakeholders to solve problems related to post-disaster sanitation. Dusun 1 was chosen to be the location of domestic wastewater distribution and treatment because of the low difference in land elevation, by following the existing road in Dusun 1, the highest elevation point is about 690 metres and the lowest point is about 545 metres. Dusun 1 is divided into four planning blocks. The specific development location will be prioritised to be implemented in Block 4 considering several aspects. There is a vacant land of 1,169 m2 owned by the village so that it can be utilised without incurring land acquisition costs. For the elevation of the highest pipeline to the WWTP is 580 metres and the lowest is 553 metres, the treatment results are planned to be discharged back into the water body, namely the river near the WWTP location. The planning period is carried out for 10 years (2024 - 2034) by serving 100% of the population of Block 4 and 56% of the population of Dusun 1 by serving the total population in 2034 based on population projections of 5,385 people. The wastewater distribution system uses shallow bore sewer with a generation of 377.61 m3/day and piping using a type of PVC pipe diameter of 4’ or 160 mm as many as five lines with soil excavation in the range of 0.56 - 6.81m. The selected domestic wastewater treatment technology configuration based on Simple Additive Weighting and will be applied in Wangunjaya Village is ABR and Aerobic Filter as the main technology using the principle of a combination of physical and biological treatment. The overall configuration of the treatment unit starts from an integrated Bar Screen and Equalisation Tank, then enters the First Sedimentation Tank, ABR, Aerobic Filter, Second Sedimentation Tank, Sludge Collection Tank, and the disinfection process is carried out before being returned to the environment in the form of effluent. Regarding the cost of planning the construction of SPAL and IPAL, the Budget Plan (RAB) requires a construction cost of Rp2,026,174,000.00. Operational and maintenance costs for the SPAL and WWTP are Rp96,612,000 per year. Financial analysis is required to determine the feasibility of project implementation from an economic aspect. There are two determining variables commonly used to determine the economic feasibility of a project, namely Net Present Value (NPV) and Benefit Cost Ratio (BCR). The NPV value is Rp165,021,444.25 or positive NPV, the BCR value is 1.232. Both values indicate that the WWTP planning project is economically feasible.